Pharmacovigilance in Serbia: a Ten-Year Pharmacoepidemiologic Analysis - Dejan Živanović; Vesna Mijatović Jovin; Jovan Javorac; Isidora Samojlik; Aleksandar Rašković; Marija Jevtić; Svetlana Stojkov; Nataša Jovanović Lješković; Nataša Perković Vukčević (Acta Clinica Croatica, 2023)
Pharmacovigilance as a science and group of activities related to detection, collection, analysis, understanding and prevention of adverse drug reactions (ADRs) is an essential activity in the regulatory system of drugs of any country. Defining increased patient safety as the main purpose of ADR reporting, a well-designed national pharmacovigilance system achieves its ultimate goal, i.e., protection of public health. In organizational and technical terms, the Republic of Serbia has a well-developed system of pharmacovigilance, created on the basis of a proven reliable system of the former SFR Yugoslavia, and carried out by the National Agency for Medicines and Medical Devices of Serbia (ALIMS), which conducts all organized activities aimed at strengthening the national system of ADR monitoring and reporting. Unlike the neighboring Croatia and Montenegro with similar pharmacovigilance systems, Serbia has only recently approached the WHO standard of 200 reports per million inhabitants despite a significant increase of 180 ADR reports per million inhabitants in 2019 (1251 in total). Considering this, our study aimed to provide a critical insight into the practice of pharmacovigilance in Serbia by pharmacoepidemiologic analysis of a ten-year period of ADR monitoring and reporting activities.